2007
DOI: 10.1007/s00125-006-0585-9
|View full text |Cite
|
Sign up to set email alerts
|

Increasing prevalence of type 2 diabetes in a Scottish population: effect of increasing incidence or decreasing mortality?

Abstract: Aims/hypothesis We examined incidence, prevalence and mortality from type 2 diabetes mellitus in a Scottish population over 12 years, and evaluated the effects on prevalence of increasing incidence and decreasing mortality. Materials and methods We used a diabetes clinical information system in Tayside (population 387,908), Scotland, to identify new cases of type 2 diabetes between 1993 and 2004 and to calculate incidence rates and mid-year prevalence. We defined mortality rates as the number of deaths of diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
55
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 10 publications
11
55
1
2
Order By: Relevance
“…This has shown [14] a similar prevalence of diabetes in 1996 (1.94% compared with 1.89% in Denmark) and similar increase in prevalence (6.7% per year compared with 6.3% per year [men] and 6.6% per year [women] in Denmark). In the Skaraborg region (population about 300,000) of Sweden, a registry based on clinical recordings from patients [15] showed a prevalence of 3.2% in 1995, somewhat higher than found in Denmark.…”
Section: Discussionmentioning
confidence: 82%
“…This has shown [14] a similar prevalence of diabetes in 1996 (1.94% compared with 1.89% in Denmark) and similar increase in prevalence (6.7% per year compared with 6.3% per year [men] and 6.6% per year [women] in Denmark). In the Skaraborg region (population about 300,000) of Sweden, a registry based on clinical recordings from patients [15] showed a prevalence of 3.2% in 1995, somewhat higher than found in Denmark.…”
Section: Discussionmentioning
confidence: 82%
“…Explanations for the differing prevalence and incidence estimates of type 2 diabetes could also be influenced by demographic changes (such as an ageing population and immigration), effects of changes in treatment patterns (such as earlier GLD initiation [6]) and increased survival rates in the diabetes population. Studies from Canada, Finland, the UK and the USA have reported declining all-cause mortality in the diabetic population but increasing incidence of diabetes [4,[21][22][23], suggesting that there has been successful treatment of diabetes and diabetes-related complications but insufficient lifestyle-changing programmes to prevent diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Esse padrão de distribuição das taxas de mortalidade não acompanha, de modo geral, aquele evidenciado em estudos epidemiológicos realizados em diferentes países que constataram a redução da mortalidade por diabetes melito nas últimas décadas, embora com aumento da sua incidência e prevalência (4,6,14,15). Entre as possíveis explicações para esse declínio, são apontadas tendências de redução da mortalidade por doença coronariana e por acidente vascular cerebral, menor exposição a fatores de risco como o tabagismo, busca ativa de casos e rastreamento levando ao diagnóstico mais precoce da doença e intervenções médicas para redução dos níveis de glicemia, colesterolemia e pressão arterial (5,26).…”
Section: Discussionunclassified
“…A prevalência de diabetes melito no Brasil correspondeu a 7,6% em um estudo realizado com amostra representativa da população urbana entre 30 e 69 anos de idade (13), apresentando magnitude comparável à de países da Europa e da América do Norte (4,6,14). Indivíduos com diabetes apresentam maior risco de vida, principalmente, por alterações cardiovasculares circulatórias e renais (15,16).…”
unclassified